Logical methods: in honor of Anil Nerode’s sixtieth birthday - Crossley, John N.; Remmel, Jeffrey B.; Shore, Richard; Sweedler, Moss E. (Progress in computer science and applied logic, 1993)
The Work of Anil Nerode: A Retrospective -- Embedding Distributive Lattices Preserving 1 Below A Nonzero Recursively Enumerable Turing Degree -- Prime Isols and the Theorems of Fermat and Wilson -- Problem Solving Strategies for the Derivation of Programs -- Effective Real Dynamics -- An Integer Lattice Arising in the Model Theory of Wreath Products -- Undecidability and Definability for Parametrized Polynomial Time m-Reducibilities -- Extracting Programs from Proofs by an Extension of the Curry-Howard Process -- A Bird’s-Eye View of Twilight Combinatorics -- Effectively and Noneffectively Nowhere Simple Subspaces -- Index Sets in Recursive Combinatorics -- Computability in Unitary Representations of Compact Groups -- Recursive Properties of Intervals of Recursive Linear Orders -- Algorithmic Stability of Models -- The Combinatorics of the Friedberg-Muchnick Theorem -- Partial Automata and Finitely Generated Congruences: An Extension of Nerode’s Theorem -- Minimal Pair Constructions and Iterated Trees of Strategies -- Intuitionistic L -- n-Recursive Linear Orders Without (n + 1)-Recursive Copies -- Multiple Agent Autonomous Control — A Hybrid Systems Architecture -- Distributed Concurrent Programs as Strategies in Games -- Dempster-Shafer Logic Programs and Stable Semantics -- Who Put the “Back” in Back-and-Forth? -- Polynomial Time Categoricity and Linear Orderings -- The Disjunction and Numerical Existence Properties for Intuitionistic Analysis -- On the Strength of Fraïssé’s Conjecture.